PENERAPAN PEMBELAJARAN STEAM MELALUI METODE PROYEK DALAM MENINGKATKAN KREATIVITAS ANAK USIA DINI DI TK PELITA - Nurinayah, Astri Yansyah; Nurhayati, Sri; Wulansuci, Ghina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
This research was motivated by the low creativity of children in Pelita Kindergarten, this is because the variety of playing in learning is still monotonous using children's worksheets. In finding solutions to problem-solving teachers apply STEAM learning through the project method. The purpose of this study was to determine the description of the application of STEM learning in improving children's creativity in TK Pelita. This research uses a qualitative approach with descriptive statistical methods. The data collection technique used in this study was through triangulation, namely through observation, interviews, and documentation studies. The research subjects were the principal, teachers, and children in group B. Data analysis was carried out through data collection, data reduction, data grouping, data presentation, and concluding. The application of STEAM learning through the project method in TK Pelita is carried out through the following stages: 1) preparing a project plan. 2). Create a project implementation schedule. 3) carry out the project. 4). monitor child and project progress. 5) assessment of results. The results of research on the application of Engineering Science and Engineering Mathematical Science learning through the project method at Pelita Kindergarten can develop children's learning activities and increase children's creativity.Penelitian ini dilatar belakangi oleh rendahnya kreativitas anak di TK Pelita, hal ini disebabkan ragam main dalam pembelajaran masih monoton menggunakan lembar kerja anak. Dalam mencari solusi pemecahan permasalahan guru menerapkan pembelajaran STEAMmelalui metode proyek. Tujuan penelitian ini untukmengetahui gambaran tentang penerapan pembelajaran STEAMdalam meningkatkan kreativitas anak di TK Pelita. Penelitian ini menggunakan pendekatan kualitatif dengan metode statistik deskriptif. Teknis pengumpulan data yang digunakan dalam penelitian ini melalui tri angulasiyaitu melalui kegiatan observasi, wawancara dan studi dokumentasi.Subjek penelitiannya adalah kepala sekolah, guru-guru dan anak-anak di kelompok B. Analisis data dilakukan melalui pengumpulan data, reduksi data, pengelompokan data,penyajian data serta penarikan kesimpulan. Penerapan pembelajaran STEAMmelalui metode proyek diTK Pelitadilakukan melalui tahapan: 1) menyusun perencanaan proyek. 2). Membuat jadwal pelaksanaan proyek. 3) melaksanakan proyek. 4). memantau anak dan kemajuan proyek. 5) penilaian hasil.Hasil penelitian tentang Penerapan pembelajaran Sains Technologi Engineering Art Matematicmelalui metode proyek di TK Pelita dapat mengembangkan aktifitas pembelajaran anak sertakreativitas anak meningkat.